Net Migration, Endogenous Incomes and the Speed of Adjustment to the North-South Differential - Dunlevy, James A.; Bellante, Don (The Review of Economics and Statistics, 1983)
James A. Dunlevy, Don Bellante, Net Migration, Endogenous Incomes and the Speed of Adjustment to the North-South Differential, The Review of Economics and Statistics, Vol. 65, No. 1 (Feb., 1983), pp. 66-75